1998
DOI: 10.1046/j.1365-2044.1998.00307.x
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal diamorphine for analgesia after Caesarean sectionA dose finding study and assessment of side‐effects

Abstract: SummaryEighty women undergoing elective Caesarean section under spinal anaesthesia using hyperbaric bupivacaine 0.5% were randomly allocated to receive, in addition, intrathecal diamorphine 0.125, 0.25 or 0.375 mg or saline. Postoperative morphine requirements, measured using a patientcontrolled analgesia system, were reduced in a dose-dependent manner by diamorphine. Pain scores were significantly lower at 2 and 6 h following the two larger doses of diamorphine. Less supplemental analgesia was required intra-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(29 citation statements)
references
References 26 publications
0
29
0
Order By: Relevance
“…Recent studies have shown diamorphine to be as effective as morphine for analgesia after surgery [8,9]. The optimum dose of diamorphine is between 0.25 and 0.375 mg, with more side-effects at the higher end of the dose range [20,21]. Patients receiving intrathecal diamorphine receive less supplemental analgesia during surgery [12,20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown diamorphine to be as effective as morphine for analgesia after surgery [8,9]. The optimum dose of diamorphine is between 0.25 and 0.375 mg, with more side-effects at the higher end of the dose range [20,21]. Patients receiving intrathecal diamorphine receive less supplemental analgesia during surgery [12,20].…”
Section: Discussionmentioning
confidence: 99%
“…The optimum dose of diamorphine is between 0.25 and 0.375 mg, with more side-effects at the higher end of the dose range [20,21]. Patients receiving intrathecal diamorphine receive less supplemental analgesia during surgery [12,20]. Furthermore, Husaini demonstrated a decrease in unwanted side-effects with diamorphine, especially pruritus [8].…”
Section: Discussionmentioning
confidence: 99%
“…In a doubleblind study of primigravidae, epidural diamorphine has been found to effective for pain relief in labour [29]. Diamorphine has been used after Caesarean section for analgesia [30], and has been found to be safe in a double-blind study of patients undergoing Caesarean section with pain scores and other adverse effects reduced in a dose-dependent manner by intrathecal diamorphine [31]. It is an indication of the relaxed attitude of British physicians to diamorphine that it is also used with newborn infants and with children.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 In addition, when inducing spinal anaesthesia in the sitting position, the specific technique, the drugs used and their doses are critical otherwise there is considerable potential for the spinal to fail. [20][21][22] Such critical reliance on the technicalities is much less important when a lateral position is used.…”
Section: Sitting Position and Anaesthetist Harmmentioning
confidence: 99%